Rapid and Reliable Assessment of Fish Physiological Condition for Fisheries Research and Management Using Fourier Transform Near-Infrared Spectroscopy - Goldstein, Esther D.; Helser, Thomas E.; Vollenweider, Johanna J.; Sreenivasan, Ashwin; Sewall, Fletcher F. (Frontiers in Marine Science, 2021)
Measuring fish population responses to climate change requires timely ecological information, warranting innovative approaches to data collection in fisheries research and management. Fourier transform near-infrared spectroscopy (NIR) is a promising tool to efficiently and cost-effectively obtain multiple types of fisheries data including fish physiological health and energetics that can provide indicators of stock status and environmental change. We tested the applicability of NIR to determine fish physiological state and condition by developing NIR calibration models for morphometric indices of body condition (Fulton’s K and hepatosomatic index), biochemical measurements of tissue composition (lipid content and energy density), and a nucleic acid-based index of recent growth (RNA:DNA) of juvenile Pacific cod (Gadus macrocephalus). NIR spectral data had the best predictive ability for lipid content followed by energy density, and weak relationships with morphometric indices and RNA:DNA. For both energy density and lipid content, the most informative wavenumber regions in the spectral data were associated with carbon-hydrogen bonds in lipid molecules. Additionally, NIR calibration models better predicted lipid content than morphometric measurements that are often used as proxies for measuring energy reserves, indicating that NIR might serve as a more informative index of body condition and energy stores than other rapid methods. Efficient sample analysis by NIR can supplement traditional metrics of body condition and be especially useful for ensuring the availability of monitoring data in support of fisheries research and management.